Minimization of the surface roughness and form error on the milling of free-form surfaces using a grey relational analysis - KURT, MUSTAFA; MUTLU MİTİL, BİLÇEN (My University, 2012)
The aim of this paper is to assess an experimental analysis of different tool-path strategies with respect to their influences on surface roughness and dimensional machining errors during free-form surface machining using experimental works. For this purpose, the machining of Al7075-T651 material, which is used in the production of free-form surfaces for the die-sinking sector, in particular, was examined using a ball-end mill in a 3-axis CNC machine. The effects of the tool diameters and of the rough and finished machining strategies on the presence and character of form errors and surface roughness were investigated and the results were optimized using a Grey Relational Analysis. The results obtained from these experiments clearly indicate the influence of tool-path strategies and tool diameters on form errors, as well as the importance of the appropriate strategies for reducing the surface roughness.
Keywords: Kimya; Fizikokimya; Polimer Karakterizasyonu; Temel Bilimler; Mühendislik ve Teknoloji; Chemistry; Physical Chemistry; Characterization of Polymers; Natural Sciences; Engineering and Technology; Mühendislik, Bilişim ve Teknoloji (ENG); Temel Bilimler (SCI); Malzeme Bilimi; POLİMER BİLİMİ; MALZEME BİLİMİ, ÇOKDİSİPLİNLİ; Engineering, Computing & Technology (ENG); Natural Sciences (SCI); MATERIALS SCIENCE; CHEMISTRY; POLYMER SCIENCE; MATERIALS SCIENCE, MULTIDISCIPLINARY; Polimerler ve Plastikler; Fizik Bilimleri; Metaller ve Alaşımlar; Polymers and Plastics; Physical Sciences; Metals and Alloys; Form error; Free-form surface; Milling; Surface roughness